Features of mechanical ventilation in acute respiratory distress syndrome complicated by bronchopulmonary fistula (case report) - K. V. Pshenisnov; Yu. S. Aleksandrovich; E. Yu. Felker; E. M. Dmitrieva; A. V. Meshkov; M. V. Razgon; N. M. Solomatina; O. D. Storozhuk; V. S. Potapov (Вестник анестезиологии и реаниматологии)
Introduction. Acute respiratory distress syndrome is one of the most formidable complications of critical conditions in children, leading to severe systemic hypoxia and associated with a high probability of death.The objective was to demonstrate respiratory support characteristics in acute respiratory distress syndrome complicated by bronchopulmonary fistula in a child with sepsis.A clinical case was used to illustrate the main principles of invasive invasive artificial lung ventilation in severe hypoxemic respiratory failure due to pneumonia caused by Streptococcus pyogenes. The basic data of the history, clinical and laboratory examination were reflected, special attention was paid to the intensive care measures and the choice of the optimal mode of invasive invasive artificial lung ventilation, which allowed to achieve the target indicators of the gas composition and the acid-basic state of the blood.Conclusion. In severe acute respiratory distress syndrome in children, it is advisable to perform invasive artificial lung ventilation with inspiration control by pressure and guaranteed respiratory volume at a positive end expiratory pressure of at least 6 sm H2O. The use of inspiration/expiration ratio reversal can only be justified in extremely rare cases as a life-saving measure in the absence of persistent hypercapnia.